Expert System for Diagnosing the Level of Online Game Addiction in Malikussaleh University Students with Certainty Factor Method - Melia Rahma Amini Simanjuntak; Rizky Putra Fhonna; Muthmainnah Muthmainnah (Proceedings of International Conference on Multidisciplinary Engineering (ICOMDEN), 2024)
Online gaming has become one of the most popular forms of entertainment, especially among university students. However, online game addiction can have negative impacts such as social isolation and mental health disorders. This research aims to design and build an expert system that can diagnose the level of online game addiction in Malikussaleh University students using the Certainty Factor method. This method was chosen because it is able to measure the level of confidence in decision making based on evidence or expert judgment. The expert system developed will provide diagnoses based on the symptoms of addiction identified. This research uses primary data obtained through interviews with experts and observations, as well as secondary data from literature studies. The results of this study are that out of 250 samples of malikussaleh university student data, 44 people or 17.6% of the sample experienced mild addiction, 81 people or 32.4% of the sample experienced moderate addiction, and 125 people or 50% of the sample experienced severe addiction to online games. This shows that this expert system can be used to facilitate users in detecting the level of addiction to playing online games they suffer. The results of this study are expected to help students to know their level of addiction to online games, so that appropriate prevention and control measures can be taken. In addition, this research is also expected to contribute to the development of expert systems in the field of mental and behavioral health. Thus, this expert system can be an effective tool in diagnosing and overcoming online game addiction among students. Keywords: System, Expert, Addiction, Certainty Factor